When death strikes early as often will: How counsellors and schools can support grieving pupils and students. (March 2023) - Wango, Geoffrey; Gwiyo, Leila Mkameli
Death is inevitable and universal, and the corona virus disease has only further intensified a world of uncertainties as a result of frequent accidents, HIV/AIDS, cancer and natural disasters. Bereavement after any death is a potentially disruptive life event with consequences in physical and mental health, relationships and social functioning. Death is a rather odd, thought-provoking and challenging experience, particularly in the lives of children and adolescents. Death of parent/s, sibling, relative/s, teacher, classmate or friend is a relatively new and challenging phenomenon. Persons working with pupils and students, including teachers, counsellors, school chaplain and social workers, need to be prepared to offer help to those who experience bereavement. Death is unpredictable and may occur naturally, suddenly, or traumatically. In several instances, help is sometimes required in advance of bereavement in that the death may be anticipated such as instances of prolonged illness or following a fatal accident. In all cases, the role of the teacher and counsellor in the school is pivotal in supporting pupils and students who have been bereaved. This paper highlights the need to impart post-traumatic growth in bereft pupils and students in schools in order to cope with bereavement.